The accuracy of seminumerical reionization models in comparison with radiative transfer simulations. Issue 2 (15th March 2018) - Hutter, Anne
Abstract: We have developed a modular seminumerical code that computes the time and spatially dependent ionization of neutral hydrogen (${\rm H}\, \rm {\small {I}}$ ), neutral (${\rm He}\, \rm {\small {I}}$ ), and single-ionized helium (${\rm He}\, \rm {\small {II}}$ ) in the intergalactic medium (IGM). The model accounts for recombinations and provides different descriptions for the photoionization rate that are used to calculate the residual ${\rm H}\, \rm {\small {I}}$ fraction in ionized regions. We compare different seminumerical reionization schemes to a radiative transfer (RT) simulation. We use the RT simulation as a benchmark, and find that the seminumerical approaches produce similar ${\rm H}\, \rm {\small {II}}$ and ${\rm He}\, \rm {\small {II}}$ morphologies and power spectra of the ${\rm H}\, \rm {\small {I}}$ 21 cm signal throughout reionization. As we do not track partial ionization of ${\rm He}\, \rm {\small {II}}$, the extent of the double-ionized helium (${\rm He}\, \rm {\small {III}}$ ) regions is consistently smaller. In contrast to previous comparison projects, the ionizing emissivity in our seminumerical scheme is not adjusted to reproduce the redshift evolution of the RT simulation, but directly derived from the RT simulation spectra. Among schemes that identify the ionized regions by the ratio of the number of ionization and absorption events on different spatial smoothing scales, we find those that mark the entire sphere as ionized when the ionization criterion is fulfilled to result in significantly accelerated reionization compared to the RT simulation. Conversely, those that flag only the central cell as ionized yield very similar but slightly delayed redshift evolution of reionization, with up to 20 per cent ionizing photons lost. Despite the overall agreement with the RT simulation, our results suggest that constraining ionizing emissivity-sensitive parameters from seminumerical galaxy formation-reionization models are subject to photon nonconservation.